An energy-based method to calculate the vulnerability scores of RC buildings for rapid structural assessment methods. (July 2022) - Demirbas, Nurbanu; Durucan, Cengizhan; Sahin, Humeyra
Abstract: In this study, the some of the vulnerability scores commonly used in rapid structural assessments methods are obtained by an energy based method. For this purpose, non-linear time history and non-linear pushover analyses of several 2D frames with different structural and dynamic properties are performed. Both of the material and geometric nonlinearity are considered in the structural models. The non-linear time history analyses are performed with response spectra compatible far fault ground motion records. The analyses results revealed that the vulnerability score of soft story formation may be improved by considering it in a parametric manner instead of using a constant vulnerability score. The presence of brick masonry infill walls reduces the negative effect of soft story formation. The presence of weak story formation (for the considered case) also affects the earthquake performance of structure but this negative effect is not considerable as that of soft story formation. The combined effect of structural deficiencies can be more significant than the values of vulnerability scores calculated by summing the vulnerability score of each structural deficiency.